Intervention of cooperatives and services for SMEs resilience in Surakarta City - Winduro, Wirid; Suhita, Damayanti (Publisia: Jurnal Ilmu Administrasi Publik, 2023)
According to Government Regulations No. 7 of 2021, it’s essential for the gov-ernment to help small and medium-sized enterprises (MSMEs) that have beenstruggling due to the Covid-19 pandemic. This study investigates the interven-tion of the Department of Cooperatives and SMEs in Surakarta City to promoteMSME resilience during the pandemic. The research uses a qualitative ap-proach to examine the situation on the ground, using data from primary andsecondary sources such as the Surakarta City Cooperation and SMEs Office,Manahan Village, and MSME business owners. The findings indicate that theSurakarta City Cooperation’s and SME Service has been following thegovernment’s policies during the pandemic. However, their efforts to supportMSMEs in 2020 and 2021 were hampered by resource constraints caused bythe Covid-19 outbreak. Despite these challenges, the Surakarta CityCooperation’s and SME Service distributed aid from the Ministry of Coopera-tives and SMEs to local business owners. Once the pandemic situation stabi-lized, the Surakarta City Cooperations and SME Service started to provideassistance to MSMEs to help them recover, but due to limited resources, only afew businesses received support. Nonetheless, most MSMEs were able to re-cover on their own.